(untitled) (Journal of Education and Development, 2020)
Ongoing reports of the achievement gap suggest the need for effective interventions that can increase motivation and academic outcomes for African-American youth. This study describes a 3-week evidence-based attribution retraining intervention designed to alter harmful beliefs associated with academic failure among African-American middle school students. Guided by attribution theory, the lessons in the intervention were designed to help students modify maladaptive attributions for academic failure and understand that positive academic outcomes could be obtained through increased preparation and effort. Participants included 64 6th graders identified as low achieving who were randomly assigned to either a treatment or wait-list control group. Results showed significant increases in adaptive attributions and decreases in maladaptive attributions for the treatment group compared to the control group. Implications for policy and practice are discussed.